A comparative and correlative study of the Voice-Related Quality of Life (V-RQOL) and the Voice Activity and Participation Profile (VAPP) for voice-related quality of life among teachers with and without voice disorders. Issue 9 (March 2019) - Yu, Lingyu; Lu, Dan; Yang, Hui; Zou, Jian; Wang, Haiyang; Zheng, Meijun; Hu, Juanjuan
Abstract : Abstract: The aim of this study was to investigate the difference and correlation between the Voice-Related Quality of Life (V-RQOL) and the Voice Activity and Participation Profile (VAPP) among teachers. The participants were 672 teachers (218 males and 454 females, male-to-female ratio = 0.48:1) whose vocal cords were examined using a Strobolaryngoscope. Questionnaire results were obtained for both the V-RQOL and the VAPP. Of the 672 participants, 322 teachers had voice disorders while 350 teachers did not. The most common voice complaint was hoarseness (n = 250), and the most common throat complaint was foreign body sensation (n = 129) in teachers with voice disorders. Chronic laryngitis (n = 162, 50.3%), vocal cord polyps (n = 92, 28.6%), and vocal cord nodules (n = 43.13.4%) were the most frequent diagnoses in teachers with voice disorders. Significant differences were seen on the V-RQOL and the VAPP scores between teachers with and without voice disorders, and between female and male teachers. Differences were also observed among teachers from different grades, and among different types of voice-related diseases. Moderate-to-strong correlations were observed between the VAPP total score and those for all the subscales of the VAPP and between the VAPP total score and the V-RQOL score ( P  < .001). Teachers with voice disorders have a significantly poorer voice-related quality of life than those without voice disorders, as do female teachers compared with male teachers. Different groups of voice disorders have different effects on teachers' voice-related quality of life, and primary school teachers suffer from a poorer voice-related quality of life than do high school teachers. A moderate-to-strong correlation was found between the results of the V-RQOL and the VAPP scores.